Sintomas de depressão e transtornos psiquiátricos menores e indivíduos com e sem disfonia - Monteiro, Cláudia Quézia Amado (2017)
This dissertation aimed to relate mental health disorders (Minor Psychiatric Disorders and symptoms of depression) with dysphonia. This manuscript is subdivided into three articles. A theoretical article that sought to investigate the literature about the relationship between depression and dysphonia. A second article analyzed the relation of minor psychiatric disorders and symptoms of depression in patients with and without dysphonia. Finally, a third article that verified the prediction of minor psychiatric disorders and depressive symptoms for the development of dysphonia. The empirical articles have as data collection variables of mental health (Self-Reporting Questionnaire - SRQ-20 and Beck Depression Inventory - BDI) and vocals (Scale of Vocal Symp- toms and perceptive auditory analysis) of 130 subjects with and without dysphonia. The main results reflect an important relation of the investigated emotional factors and the dysphonia. The dysphonic individuals showed more symptoms of depression, anxiety and somatization when compared to non-dysphonic ones. In addition, minor psychiatric disorders were presented as risk factors for dysphonia.